GE_GERICHTE C/4760/2012 vom 22. Juli 2014 - GE Cour de justice (2014)
LOCAL PROFESSIONNEL; BAIL À LOYER; RÉSILIATION ABUSIVE; PROLONGATION DU BAIL À LOYER | CO.271a.1.e; CO.271.3; CO.271; CO.272.1; CPC.95.1